Mucormycosis in Post Covid Patient - A Case Report - Kush Pathak; Asha Karadwal; Prachi Nayak; Sushruth Nayak (Indian Journal of Forensic Medicine & Toxicology, 2021)
Mucormycosis is considered to be a rare notorious fungal infection mainly affecting diabetics with or withoutketoacidosis & immunocompromised patients, with high mortality rate. Occurrence of Mucormycosis as animplication of Covid-19 has not yet been reported. We present a case of aggressive mucormycosis in a Postcovid-19 type-2 diabetic patient and aim to illustrate the possible Covid-19 effects on body and a dire needfor early diagnosis.